The Interaction Effects of Mood and Ad Appeals on Type of Elaboration and Advertising Effectiveness. Issue 1 (2nd January 2017) - Wen, Jing (Taylor); Sar, Sela; Anghelcev, George
ABSTRACT: An experiment was conducted to examine how mood (positive vs. negative) and ad appeals (experiential vs. utilitarian) influence ad and product evaluation and purchase intention. Specifically, mood and ad appeals both influenced type of elaboration (relational vs. item-specific processing). As a result, people in a positive mood evaluated ad and product more positively when exposed to a utilitarian ad, whereas people in a negative mood evaluated ad and product more positively when exposed to an experiential ad. Also, people in a negative mood showed stronger purchase intention when exposed to an experiential ad. Theoretical and practical implications are also discussed.